Konsep Hibah Bersyarat Sebagai Pencegahan Terjadinya Sengketa Waris di Pengadilan Agama - Solehah, Siti Afifah; Abdul Kadir Sabaruddin; Musthafa (Indonesian Journal Publisher, 2025)
This study examines conditional grants (hibah bersyarat) as a preventive mechanism to prevent inheritance disputes in the Religious Courts. The high number of inheritance dispute cases submitted to the courts indicates weaknesses in the regulation and planning of family asset management. On the other hand, the practice of fully transferring assets to children during the lifetime of parents has the potential to create legal vulnerability and future conflicts, particularly when the donor loses control over assets that have already been transferred. These conditions underline the need for alternative legal arrangements that are capable of providing legal protection for donors while simultaneously ensuring legal certainty for recipients. This research aims to analyze the concept of conditional gifts from normative and juridical perspectives and to assess their effectiveness as an instrument of legal protection, as well as a means to realize justice, legal certainty, and utility in family asset management. The study employs a normative legal research method using conceptual and statutory approaches, supported by empirical data obtained through interviews with notaries as a means to strengthen the analysis and to obtain practical perspectives regarding the implementation of the examined legal concept. The findings confirm that conditional gifts are normatively legitimate and legally acceptable, allow donors to retain control, provide early certainty, and function as an effective mechanism to prevent inheritance disputes.